Manajemen strategi SDM dalam bank syariah: Upaya meningkatkan kapabilitas organisasi - salsabila, eliza (Maliki Interdisciplinary Journal, 2025)
The development of Islamic banking in Indonesia has shown significant growth in line with the increasing public awareness of Islamic financial principles. Amidst intense competition and massive digital transformation, strategic human resource management (HRM) has become a crucial factor in strengthening organizational competitiveness and capability. This study aims to analyze how HRM strategies in Islamic banks contribute to enhancing organizational capability through competency development, Islamic work culture, and adaptation to technological advancement. The research employs a qualitative approach with a descriptive-analytical method based on a literature review of eleven relevant academic sources. The findings reveal that the implementation of HRM strategies grounded in Islamic values creates a balance between professionalism and spirituality at work. Such strategies foster a productive, innovative, and equitable organizational culture. Furthermore, digital transformation and innovation in HRM practices expand the organizational capability of Islamic banks to adapt to the dynamics of the modern financial industry. Therefore, strengthening HRM strategies based on Islamic principles serves as a strategic effort to achieve sustainable competitive advantage in the Islamic banking sector.